The expert advantage. The official blog of the Pathways to the Podium Research Project (2011)
The Pathways to the Podium Research Project is a multi-sport, multi-national investigation of the development of sport expertise, conducted by a team of sport scientists from Victoria University, Australia, York University, Canada, and the Australian Institute of Sport. The project aims to gain an understanding of the pathways that athletes follow on their way towards attaining peak performance. Most importantly, we are interested in how the pathways of elite athletes differ from those of lesser skilled athletes. The information obtained from this research will be used to provide recommendations relating to the conditions of sport participation and practice that are optimal for the development of sport expertise.